Systematic Literature Review: The Effectiveness of the Jigsaw Cooperative Learning Model on the Formation of Islamic Character in Elementary Schools - Muhammad Zainul Ramdani (Journal of Islamic Religious Studies, 2026)
This study aimed to systematically analyze the effectiveness of the Jigsaw cooperative learning model in fostering Islamic character among elementary school students. The study was conducted in response to the growing need for instructional approaches that integrate academic achievement with moral, social, and spiritual development in elementary education. A qualitative approach using a Systematic Literature Review (SLR) design was employed in this study. The data were collected from scientific journal articles, conference proceedings, and scholarly books published between 2015 and 2025, obtained from academic databases such as Google Scholar, Scopus, ERIC, Dimensions, and Crossref. A total of 30 selected studies were analyzed using thematic analysis techniques through systematic stages of identification, screening, eligibility assessment, data extraction, and synthesis. The findings revealed that the Jigsaw cooperative learning model significantly improves students’ active participation, academic achievement, classroom interaction, collaboration, and peer learning experiences. Furthermore, the model contributes positively to the formation of Islamic character values, including responsibility, discipline, empathy, cooperation, tolerance, moral behavior, and ukhuwah among elementary school students. The review also identified several supporting factors, such as teachers’ competence and classroom support, as well as challenges related to student participation, time management, and limited theoretical integration between cooperative learning and Islamic character education. This study concludes that the Jigsaw cooperative learning model is an effective collaborative learning strategy for integrating academic learning with Islamic character formation in elementary educational contexts.